EXPERIMENTAL AND FINITE ELEMENT ANALYSIS OF HUMAN INJURY PREDICTION SUBJECTED TO UNDERBELLY BLAST LOADING - Khalis Suhaimi (Tesis, 2019)
One of the lethal threats faced by an armoured vehicle comes from explosion of a land time. The blast wave from the explosion propagates to the vehicle structure, floor, seats and eventually to the occupants inside the vehicle.If blast waves are not dissipated properly, it coould bring harm to occupants. In this study, the occupant response during mine blast was investigated using experimental test and numerical simulation.